1954
DOI: 10.1021/jf60044a005
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Carotene, Quinoline Derivatives as Antioxidants for Carotene

Abstract: Because carotene stabilization in alfalfa meal is an important problem and because 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline had proved to be an effective antioxidant, a study was made of the ability of certain related chemicals to inhibit oxidation of carotene. The compounds tested were chosen to permit observation of variation in activity with systematic variation in structure. Several were effective in both dehydrated alfalfa meals and mineral oil solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1958
1958
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Of these, EQ was by far the superior, DPPD gave limited protection, and 7-toc, PG, 2-BHA and NDGA had no effect; all were at a level of 0.7 juM/g. These results confirm the previous observations of Thompson (1950) and Bickoff et al (1954). The addition to these of alkylamines gave no significant amount of added protection, in direct contrast to results obtained when some of these antioxidants and amines were used together in purified substrates (Olcott and Kuta, 1959;Olcott, 1962).…”
supporting
confidence: 91%
“…Of these, EQ was by far the superior, DPPD gave limited protection, and 7-toc, PG, 2-BHA and NDGA had no effect; all were at a level of 0.7 juM/g. These results confirm the previous observations of Thompson (1950) and Bickoff et al (1954). The addition to these of alkylamines gave no significant amount of added protection, in direct contrast to results obtained when some of these antioxidants and amines were used together in purified substrates (Olcott and Kuta, 1959;Olcott, 1962).…”
supporting
confidence: 91%
“…Harish et al 47 isolated and purified a natural vanillin from the methanol extract of D. hamiltonii tuberous roots which showed strong antioxidant activities in in vitro assays of lipid peroxidation inhibition and hydroxyl radical, superoxide anion and DPPH radical scavenging. The compound 1,2,3,4‐tetrahydroisoquinoline has the quinoline nucleus, and Bickoff et al 48 proved that certain related quinoline derivatives had effective antioxidant activity. Bourgou et al 49 found that vanillic acid and gallic acid contributed significantly to the antioxidant properties of methanol extracts of Nigella sativa L. shoots and roots.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of ethoxyl, an electron positive group, at the 6 position of EQ enhances the antioxidant activity (Bickoff et al, 1954) and the stability of the substituted quinoline molecule (Kilbourne et al, 1959). The delocalization of an unpaired electron over the conjugated system as well as over the nitrogen and oxygen stabilizes the electronic configuration around the nitrogen and oxygen atoms to prevent dimerization (Forrester et al, 1968;Rozantsev, 1970).…”
Section: Resultsmentioning
confidence: 99%